1996
DOI: 10.1136/bmj.313.7052.270
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing injectable and oral methadone to opiate addicts: results from the 1995 national postal survey of community pharmacies in England and Wales

Abstract: Objective-To establish the extent of prescribing injectable and oral methadone to opiate addicts and the practice characteristics and dispensing arrangements attached to these prescriptions.Design-National survey of25% random sample of community (high street) pharmacies through postal questionnaire, with four mailings.Setting-England and Wales. Subjects-i in 4 sample of all 10 616 community pharmacies, stratified by family health services authority.Main outcome measures-Data were collected on each prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 6 publications
0
95
1
2
Order By: Relevance
“…In several countries, pharmacies are involved in syringe exchange, distributing or selling low price kits containing injecting equipment, providing treatment for addiction, dispensing methadone, supervising methadone consumption, and providing information on drug misuse and HIV prevention. 12,13,[23][24][25][26] Pharmacists in our study believed that HIV/AIDS was a serious social and public health issue; they valued the work of SEPs but held a strongly negative position toward IDUs and against the idea of involving pharmacies in actual harm reduction service delivery. Resistance was explained by concerns that IDUs would steal from the pharmacy, endanger staff, and scare away other customers; these reactions are similar to those seen in other studies.…”
Section: Discussionmentioning
confidence: 74%
“…In several countries, pharmacies are involved in syringe exchange, distributing or selling low price kits containing injecting equipment, providing treatment for addiction, dispensing methadone, supervising methadone consumption, and providing information on drug misuse and HIV prevention. 12,13,[23][24][25][26] Pharmacists in our study believed that HIV/AIDS was a serious social and public health issue; they valued the work of SEPs but held a strongly negative position toward IDUs and against the idea of involving pharmacies in actual harm reduction service delivery. Resistance was explained by concerns that IDUs would steal from the pharmacy, endanger staff, and scare away other customers; these reactions are similar to those seen in other studies.…”
Section: Discussionmentioning
confidence: 74%
“…The Task Force identified the markedly higher level (compared with other countries) of methadone as the drug reported in drug overdose deaths, as later reported by Hall, Lynskey & Degenhardt [23], and also commissioned work by Janie Sheridan and myself which established the lack of supervision of consumption of methadone in England [24]. As a direct result, through new national guidelines on the management of drug dependence [21], we were able to recommend widespread introduction of supervised dosing of prescribed methadone during the early months of maintenance treatment.…”
Section: Medications Which Heal But Also Harm-a Complex Relationshipmentioning
confidence: 92%
“…90 Our analysis has shown that expansion of methadone maintenance programs is a cost-effective use of health care resources and suggests that these barriers deny access to a cost-effective therapy. In addition, alternatives to methadone maintenance, including medical models of dispensing methadone, 91 the use of levo-α− acetylmethadol (LAAM), 92 and drugs such as buprenorphine, 93 may be cost-effective. Our analysis had several limitations.…”
Section: Discussionmentioning
confidence: 99%